(untitled) - Hannam, Joyce (Oxford, 1997)
Jan lives in Oxford with his English wife Carol, and his father Josef, who is Czech. Jan was born in Prague, but he came to England with his father when he was a baby. He never knew his mother - she died soon after he was born. Carol plays the harp with an orchestra, and the orchestra is giving some concerts in Prague, Carol wants them all to go there for Christmas. Josef wa born in Prague, but he left his home city when he was a young man. He is an old man now, and he would like to see Prague again before he dies. But he isafraid. He still remenbers another Christmas in Prague, many long years ago - a Christmas that chnged his life for ever...
Keywords: English fiction,english literature - 20th century